PENGARUH MOTIVASI DAN ETOS KERJA TERHADAP KINERJA PEGAWAI KANTOR KEMENTERIAN AGAMA KABUPATEN KAPUAS - R Ramli; W Widarto (STIA Bina Banua Banjarmasin, 2020)
Abstract: This study aims to determine the effect of work motivation on employee performance at the Office of the Ministry of Religion of Kapuas Regency and to determine the effect of work ethic on employee performance at the Office of the Ministry of Religion of Kapuas Regency. The method in this research is quantitative research, with a population of employees of the Ministry of Religion Office of Kapuas Regency, amounting to 57 people. The sampling technique used was proportional stratified random sampling. Data collection techniques using questionnaires, direct interviews, documentation, and observation. While the data analysis technique uses inferential statistical analysis and multiple linear regression tests. The results showed that the first hypothesis which states partially between motivation influences the performance of the employees of the Ministry of Religion Office of Kapuas Regency because based on the results of the t-test it is known that t count> t Table. Turns out to be proven true. This is supported by the results of research using the statistical test of t hit> t table which is 2.868> t-table of 1.688, while the second hypothesis which states partially between work ethics influences the performance of the employees of the Ministry of Religion Office of Kapuas Regency because based on the test results t note that t arithmetic> t Table. turns out to be proven true. This is supported by the results of research using the statistical test of t hit> t table, namely 2.205> t-table of 1.688. Abtraksi: Penelitian ini bertujuan untuk mengetahui pengaruh motivasi kerja terhadap kinerja pegawai pada Kantor Kementerian Agama Kabupaten Kapuas dan untuk mengetahui pengaruh etos kerja terhadap kinerja pegawai pada Kantor Kementerian Agama Kabupaten Kapuas. Metode dalam penelitian ini adalah penelitian kuantitatif, dengan populasi Pegawai Kantor Kementerian Agama Kabupaten Kapuas yang berjumlah 57 orang. teknik pengambilan sampel menggunakan “proporsional stratified random sampling. Teknik pengumpulan datanya menggunakan Kuesioner, wawancara langsung, dokumentasi dan observasi. Sedangkan teknik analisa datanya menggunakan analisa statistic inferensial dan uji Regresi Linear Berganda. Hasil penelitian menunjukkan bahwa Hipotesis pertama yang menyatakan secara secara parsial antara Motivasi memiliki pengaruh terhadap Kinerja Pegawai Kantor Kementerian Agama Kabupaten Kapuas karena berdasarkan hasil uji t diketahui bahwa t hitung> t Tabel.ternyata terbukti kebenarannya. Hal ini didukung dengan hasil penelitian yang menggunakan uji statistik dari t hit > t tabel yakni2.868> t-Tabel sebesar 1.688, sedangkan Hipotesis kedua yang menyatakan secara parsial antara Etos Kerja memiliki pengaruh terhadap Kinerja Pegawai Kantor Kementerian Agama Kabupaten Kapuas karena berdasarkan hasil uji t diketahui bahwa t hitung> t Tabel.ternyata terbukti kebenarannya. Hal ini didukung dengan hasil penelitian yang menggunakan uji statistik dari t hit > t tabel yakni 2.205> t-Tabel sebesar 1.688.